Fenologia reprodutiva de espécies florestais nativas com potencial oleaginoso na Amazônia Central - Pinto, Antonio Moçambite [UNESP] (Universidade Estadual Paulista (Unesp), 2005)
Esta pesquisa teve como objetivo gerar informações básicas sobre a silvicultura das espécies florestais para possibilitar a implementação de programas de reflorestamento e recuperação de áreas degradadas na região amazônica. Trata-se de um estudo fenológico realizado pelo INPA, Manaus, Amazonas, especificamente pela Coordenação de Pesquisas em Silvicultura Tropical, ao longo de 35 anos. Este estudo analisou duas áreas de floresta amazônica, a Reserva Florestal Ducke (RFD) e a Estação Experimental de Silvicultura Tropical (EEST), no período de 1974 a 2000. O objetivo específico foi comparar os padrões fenológicos nas duas áreas experimentais, verificando sua regularidade e relação com fatores climáticos. As espécies selecionadas foram aquelas indicadas com potencial oleaginoso e ecológico, em avaliações preliminares e que estão sendo observadas para o estudo, a saber: Andiroba - Carapa guianensis Aubl.; Cumaru - Dipteryx odorata (Aubl.) Willd.; Casca preciosa - Aniba canelilla (H.B.K.) Mez e Pau rosa - Aniba rosaeodora Ducke. Foram amostrados 21 indivíduos de A. rosaeodora Ducke na RFD e cinco na EEST, e cinco indivíduos das espécies restantes em cada uma das duas áreas de estudo. Observados mensalmente com auxílio de um binóculo para o registro das fenofases (botões florais, antese, frutos imaturos e maduros). Os padrões fenológicos reprodutivos foram descritos de acordo com sua freqüência... .

This research aims to generate basic information about the silviculture of forest species to make the implementation of reforestation programs and the recovering of degraded areas in the Amazon region possible. This phenological research has been conducted by INPA, specifically by the Tropical Silviculture Research Coordination, over a period of 35 years. This study will analyze two areas in the Amazon Forest, Reserva Florestal Ducke (RFD) and Estação Experimental de Silvicultura Tropical (EEST), in the period between 1974 and 2000. The specific objective is to compare the phenological patterns in both experimental areas, verifying their regularity and relationship with climatic factors. The species selected were those indicated with oily and ecological potential in preliminary evaluations: Andiroba - Carapa guianensis Aubl; Cumaru - Dipteryx odorata (Aubl) Willd; Casca preciosa - Aniba canelilla (H.B.K.) Mez and Pau rosa - Aniba rosaeodora Ducke. It were sampled twentyone individuals of A. rosaeodora Ducke in RFD and five in EEST, and five individuals of the remaining species in each one of the two areas of study. The individuals were monthly observed with the assistance of binoculars to record the phenophases. The phenological patterns will be described with regards to their frequency, regularity and duration. The relations among the phenological data with the climatic variables were made through the non-parametric Spearman linear correlation analyses taking in consideration the climatic monthly mean values. It was observed at EEST, that the flowering of the species studied tend to occur in a period of less precipitation, except for Carapa guianensis that tended to bloom in the transition from dry season to rainy season. Whereas, for Aniba rosaeodora the flowering tended to occur in the rainy epoch and... (Complete abstract, click electronic address below).
Keywords: Ecologia vegetal; Fenologia reprodutiva; Floração; Frutificação; Reproductive phenology; Flowering; Fruiting